The effect of TTF-1 expression on ipsilateral mediastinal nodal (N2) metastases in primary adenocarcinoma of the lung - Samancilar, Ozgur; Kaya, Seyda Ors; Ceylan, Kenan; Usluer, Ozan; Yener, Ali Galip (Contemporary Oncology/Współczesna Onkologia, 2012)
Aim of the study: To study the effect of thyroid transcription factor-1 (TTF-1) expression on ipsilateral mediastinal nodal (N2) metastases in primary adenocarcinoma of the lung. Material and methods: The patients operated on with a diagnosis of primary adenocarcinoma of the lung were retrospectively analyzed and divided into two groups according to their TTF-1 expression. The relationship between TTF-1 expression and N2 metastases was evaluated. Results: There were 73 patients (58 male, 15 female) with a mean age of 58.4 ±10.2 in the study group. Sixty-six lobectomies or pneumonectomies and mediastinal lymph node dissection, and seven mediastinoscopies were performed. Positivity of the TTF-1 protein expression detected by the immunohistochemical staining of the specimens was present in 33 patients (45.2%); these patients were classified as group A and the rest of the patients as group B. Eleven patients had N2 disease in group A versus five patients in group B and the difference between the two groups was statistically significant. Conclusions : Patients with primary adenocarcinoma of the lung having TTF-1 expression are more likely to have N2 disease. They might be considered as candidates for adjuvant therapy.